Control of structures under uniform hazard earthquake excitation via wavelet analysis and pattern search method. Issue 5 (12th January 2012) - Bagheri, Abdollah; Amini, Fereidoun
ABSTRACT A new methodology for optimal control of structures under uniform hazard earthquake excitation has been presented in this study. The proposed method for generation of uniform hazard earthquake accelerograms is based on the sets of ground motions developed for the SAC Steel Project. The proposed controller employs the decomposing capabilities of wavelet analysis on uniform hazard earthquake accelerograms and the ability of the pattern search method to optimize a cost function to control response of structure. The performance and effectiveness of the presented method are applied to both single degree of freedom and multiple degree of freedom systems for the response control of uniform hazard earthquake‐excited systems. The results are compared with the linear quadratic regulator control algorithm; performance of the proposed control system has been found to be better than the linear quadratic regulator controller. Copyright © 2012 John Wiley & Sons, Ltd.